Characteristics of expanded polystyrene (EPS) and its impact on mechanical and thermal performance of insulated concrete form (ICF) system. (February 2020) - Arun Solomon, A; Hemalatha, G
Abstract: Fast track construction with enhanced quality, sustainable and environment-friendly methods and materials are much sought after in the construction industry. Insulated concrete form (ICF) is an evolving technique that could satisfy the present demand of the construction industry. ICF is a composite of concrete and expanded polystyrene (EPS), which enhances the insulation and other mechanical properties to the building. The objective of this study is to explore the compressive and flexural characteristics of EPS and ICF blocks under standard loading condition and evaluate the thermal performance of ICF panels using R-value. Plastic deformation, failure and energy absorption behavior of EPS and ICF blocks are assessed using compressive stress-strain profiles. The experimental results show that the plastic deformation of the ICF block is 78 times higher than plain concrete block. The presence of EPS in ICF helps to change the failure nature of sandwiched concrete from brittle to ductile, which is quantified in terms of plastic deformation. A simplified experimental approach is proposed to study the thermal performance of ICF panel using R-value. The proposed design is effective to measure the thermal resistance of wall panels and the obtained R-value of the ICF panel is 5.22 m 2 .K/W which is 7.9 times higher than the plain concrete panel. The higher R-value of ICF provides greater insulation to the building by keeping the controlled temperature for longer periods. This thermal insulation behavior of ICF reduces power demand and makes the building more energy-efficient. Thus the ICF system helps in sustainable building construction by affording high thermal insulation with improved structural strength.